Who, me? Optimism bias about US teenagers’ ability to quit vaping - Strombotne, K; Sindelar, J; Buckell, J (Wiley, 2021)
Background and aims The vaping rate among US teenagers has doubled in the last 2 years, which may be explained in part by teenagers’ optimism that they would have relatively little trouble in quitting. The aim of this study was to estimate the extent to which teenagers exhibited optimism bias, what characteristics are associated with optimism bias and which factors are related to respondents’ perceptions of how hard it would be for them to quit.